PHARMACOGENETIC BASES OF INDIVIDUAL SENSITIVITY AND PERSONALIZED ADMINISTRATION OF ANTIPLATELET THERAPY IN DIFFERENT ETHNIC GROUPS - B. I. Kantemirova (Farmaciâ i Farmakologiâ (Pâtigorsk), 2021)
Cardiovascular diseases (CVDs) are the leading cause of disability and mortality worldwide. Increased thrombosis is the trigger point for the development of various CVDs and their complications, and therefore, therapy with P2Y12-receptor inhibitors is always pathogenetically justified and vital. However, according to the various data, 10-25% of patients treated with clopidogrel have “resistance” to antiplatelet therapy. The causes for the formation of resistance are still not clear. There is no generally accepted, standard methodology for determining resistance to antiplatelet agents. In addition, there are no methodological approaches to identify the patients with resistance to antiplatelet drugs, and standardized schemes for correcting a low sensitivity to these drugs.The aim of this review was to summarize the available results of foreign and domestic studies devoted to the investigation of the effectiveness and safety problems of antiplatelet drugs administration from the point of view of the genetic predisposition to changes in their metabolism.Materials and methods. For the review, the following information from scientific literature represented in open and accessible sources for the period of 1996-2020, was used: pharmgkb.org, PubMed, Scopus, Web of Science Core Collection, Elibrary. Search queries – “Genetic features+antiplatelet therapy+ethnic groups”, “CYP2C19+clopidogrel+antiplatelet therapy effectiveness”; “Stent retrombosis+CYP2C19 polymorphism+ residual platelet reactivity” and “CYP2C19 polymorphism+ethnic groups+clopidogrel resistance” in both Russian and English equivalents. All these data are placed in electronic databases.Results. Currently, the problem of the resistance formation to antiplatelet drugs is studied insufficiently. The best thought-out issue is the research of the effect of the polymorphic alleles carriage of the CYP2C19 gene on the residual platelet reactivity in the patients administrated with dual antiplatelet treatment, including clopidogrel. In general, the analysis of open literature sources indicates the presence of a statistically significant association between the carrier of slow alleles of the CYP2C19 gene and the residual platelet reactivity, clinically manifested by thrombosis and adverse cardiovascular events. The occurrence frequency of polymorphic carriage of the CYP2C19 gene varies in different ethnic groups, so it cannot be extrapolated to individual subjects, peculiar in the ethnic diversity.Conclusion. To develop preventive and predictive measures aimed at overcoming resistance to antiplatelet agents, as well as working out methodological approaches to personalized prescribtion of this group drugs, a further investigation with the expansion of the search for causes and the study of the other genes participation of the cytochrome P450 system, is required.